ANTIOXIDANT CAPACITY TEST & QUALITY EVALUATION OF HAND BODY LOTION KEDONDONG JUICE (Spondias dulcis Parkinson) - Taslim, Tuty; Reny Salim; Irene Puspa Dewi; Fita Selonni (JURNAL KATALISATOR, 2024)
Kedondong (Spondias dulcis Parkinson) is a tropical fruit known for its rich vitamin C content and associated antioxidant activity. The challenges will maximize the benefits of vitamin C in kedondong fruit soluble in water, and the light will degrade and reduce its effectiveness as an antioxidant. Previous research has highlighted that the heating process affected the antioxidant activity and the ethanol extract kedondong is used to make hand body lotion. This research aims to exploit the potential of using kedondong fruit in the formulation of hand body lotion by utilizing its antioxidant activity. The study used the FRAP method using Trolox as a synthetic antioxidant so that the antioxidant capacity of kedondong juice hand body lotion is obtained which was equivalent to TEAC (Trolox Equivalent Antioxidant Capacity). The results obtained from the hand body lotion preparation of kedondong fruit juice were 4.5 mM TE⁄gram, while kedondong fruit juice was 23.04 mM TE⁄gram. The results of the quality evaluation test of hand body lotion preparations have good homogeneity, do not cause irritation, have stable pH, and have a moisturizing effect on the skin.